1997
DOI: 10.1007/bf02487827
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of single elliptic vortex rings

Abstract: The evolution of single elliptic vortex rings for initial aspect ratio (AR) =2,4,6 has been studied. The incompressible Navier-Stokes equations are solved by a dealiased pseudo-spectral method with 643 grid points in a periodic cube. We find that there are three kinds of vortex motion as AR increases and bifurcation occurs at certain AR. The processes of advection, interaction and decay of vortex ring axe discussed. Numerical results coincide with experiments and other authors' numerical simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…The crosslinking of vorticity is a cut and connect process in which the core deformation and stretching is followed by annihilation and bridging, which is completed by threading and splitting (Melande and Hussain 1989). Similar observations have been made in the work of Yao and Xungang (1997), which report that the opposite-signed vorticity (here counter rotating vortices of vortex ring) inside the contact zone gets cancelled out by viscous cross-diffusion. These cancelled vortex lines of vortex tube gets connected with their counterpart and forms isolated vortex rings.…”
Section: Higher Velocity Regionsupporting
confidence: 73%
“…The crosslinking of vorticity is a cut and connect process in which the core deformation and stretching is followed by annihilation and bridging, which is completed by threading and splitting (Melande and Hussain 1989). Similar observations have been made in the work of Yao and Xungang (1997), which report that the opposite-signed vorticity (here counter rotating vortices of vortex ring) inside the contact zone gets cancelled out by viscous cross-diffusion. These cancelled vortex lines of vortex tube gets connected with their counterpart and forms isolated vortex rings.…”
Section: Higher Velocity Regionsupporting
confidence: 73%
“…Melande and Hussain (1989) suggested that the crosslinking of vorticity is a cut and connect process in which the core deformation and stretching is followed by annihilation and bridging, which is completed by threading and splitting. Yao and Xungang (1997) observed that opposite-signed vorticity (here counter rotating vortices of vortex ring) inside the contact zone gets cancelled out by viscous cross-diffusion. These cancelled vortex lines of vortex tube gets connected with their counterpart and forms isolated vortex rings.…”
Section: Vortex Evolutionmentioning
confidence: 99%